2020
DOI: 10.1200/jco.2020.38.15_suppl.6502
|View full text |Cite
|
Sign up to set email alerts
|

Phase II/III trial of post-operative chemoradiotherapy comparing 3-weekly cisplatin with weekly cisplatin in high-risk patients with squamous cell carcinoma of head and neck (JCOG1008).

Abstract: 6502 Background: The standard treatment for post-operative high-risk patients (pts) with locally advanced squamous cell carcinoma of the head and neck (LA-SCCHN) is chemoradiotherapy with 3-weekly cisplatin (CDDP) (100 mg/m2, q3wk, 66 Gy/33Fr; 3-weekly CDDP+RT). However, one concern with 3-weekly CDDP+RT is insufficient CDDP compliance due to high-dose-related toxicities. Weekly CDDP+RT (40 mg/m2, qwk, 66 Gy/33Fr; weekly CDDP+RT) is an alternative regimen with better compliance. Here, we conducted a phase II/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
1
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 0 publications
1
39
1
1
Order By: Relevance
“…A retrospective study by Patil et al used induction chemotherapy with weekly paclitaxel and carboplatin in patients with LA-HNSCC and found that the above regimen was safe and effective even in elderly and those with poor performance status (16). Recently, the Japanese trial found that weekly cisplatin+RT is non-inferior to 3-weekly cisplatin+RT in LA-SCCHN pts and has a favorable toxicity profile, though this was reported in adjuvant setting (17). This formed the rationale for our study comparing standard 3-weekly with modified weekly TPF regimen using docetaxel at a dose of 30 mg/m 2 , Cisplatin 40 mg/m 2 and 5-FU 750 mg/m 2 , all administered weekly for 9 weeks followed by re-assessment.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study by Patil et al used induction chemotherapy with weekly paclitaxel and carboplatin in patients with LA-HNSCC and found that the above regimen was safe and effective even in elderly and those with poor performance status (16). Recently, the Japanese trial found that weekly cisplatin+RT is non-inferior to 3-weekly cisplatin+RT in LA-SCCHN pts and has a favorable toxicity profile, though this was reported in adjuvant setting (17). This formed the rationale for our study comparing standard 3-weekly with modified weekly TPF regimen using docetaxel at a dose of 30 mg/m 2 , Cisplatin 40 mg/m 2 and 5-FU 750 mg/m 2 , all administered weekly for 9 weeks followed by re-assessment.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the significant toxicities, a low-dose weekly cisplatin (30–40 mg/m 2 , administered intravenously every 7 days for the duration of radiation therapy) is frequently used in both definitive and adjuvant CRT settings, because the weekly regimen offers several advantages over the high-dose cisplatin including ease of administration and reduced toxicity [ 58 ]. A retrospective study as well as prospective Phase II/III studies comparing the efficacy of the 40 mg/m 2 cisplatin weekly and 100 mg/m 2 cisplatin every 3 weeks demonstrated non-inferiority of the weekly regimen for survival and locoregional control rates with fewer incidences of neutropenia, nephrotoxicity, and ototoxicity with low-dose cisplatin [ 59 , 60 , 61 ]. However, we need to wait for sufficient maturity of these data before suggesting changes to the current standard of care.…”
Section: Management Of Newly Diagnosed Locally Advanced Hnsccmentioning
confidence: 99%
“…At the time of this publication, the Japanese Clinical Oncology Group (JCOG) 1008 trial has been published in abstract form and showed non-inferiority of weekly cisplatin 40 mg/m 2 to three-weekly cisplatin in high-risk patients with microscopically positive margin and/or extranodal extension. 121…”
Section: Optimal Concurrent Chemotherapymentioning
confidence: 99%
“…It is noteworthy that the 30 mg/m 2 is lower than the 40 mg/m 2 commonly employed in clinical practice and the 50 mg/m 2 weekly cisplatin dose that tested favorably in the RCT comparing it to PORT‐alone, 35 discussed above. At the time of this publication, the Japanese Clinical Oncology Group (JCOG) 1008 trial has been published in abstract form and showed non‐inferiority of weekly cisplatin 40 mg/m 2 to three‐weekly cisplatin in high‐risk patients with microscopically positive margin and/or extranodal extension 121 …”
Section: Topic 1: Summary Of Studies With Oncologic Endpointsmentioning
confidence: 99%